2018
DOI: 10.3389/fimmu.2018.02614
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome Eggs Impair Protective Th1/Th17 Immune Responses Against Salmonella Infection

Abstract: Countries with a high incidence of helminth infections are characterized by high morbidity and mortality to infections with intracellular pathogens such as Salmonella. Some patients with Salmonella-Schistosoma co-infections develop a so-called “chronic septicemic salmonellosis,” with prolonged fever and enlargement of the liver and spleen. These effects are most likely due to the overall immunoregulatory activities of schistosomes such as induction of Tregs, Bregs, alternatively activated macrophages, and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…Our current understanding of helminth-bacterial co-infections lacks information on the mechanism(s) by which certain pathogenic bacteria acquire a colonization advantage during helminth infection. Some studies have attributed this to the ability of helminths to modulate immune responses that lower host defense to other bacterial pathogens [ 9 , 12 , 14 , 16 , 17 ]. Another possible mechanism by which helminths can promote bacterial infection is through shifts in the gut metabolic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our current understanding of helminth-bacterial co-infections lacks information on the mechanism(s) by which certain pathogenic bacteria acquire a colonization advantage during helminth infection. Some studies have attributed this to the ability of helminths to modulate immune responses that lower host defense to other bacterial pathogens [ 9 , 12 , 14 , 16 , 17 ]. Another possible mechanism by which helminths can promote bacterial infection is through shifts in the gut metabolic environment.…”
Section: Discussionmentioning
confidence: 99%
“…SEA was prepared by Dr Gabriele Schramm. Briefly, eggs were isolated from S. mansoni -infected hamsters as previously described ( Schramm et al., 2018 ), and then homogenized in PBS, pH 7.5, using a sterile glass homogenizer. The homogenate was then centrifuged at 21 krcf for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The secretion of antigens by helminth parasites may inhibit endotoxin-induced inflammation to dampen Th1-type responses and indirectly promote a Th2 environment in which endoparasitic helminths can thrive [61][62][63]. However, the immune system modulation/polarisation exerted by flatworms and other helminth infections can leave hosts more susceptible to secondary infections that could potentially be deleterious for both the host and parasite [64][65][66]. We have suggested that dampening classical immune activation by endotoxin with secreted molecules could be a mechanism employed by trematodes like F. hepatica and S. mansoni to confer tolerance to secondary bacterial infections [67].…”
Section: Discussionmentioning
confidence: 99%